2022
DOI: 10.1097/md.0000000000031097
|View full text |Cite
|
Sign up to set email alerts
|

Construction and analysis of heart failure diagnosis model based on random forest and artificial neural network

Abstract: Heart failure is a global health problem and the number of sufferers is increasing as the population grows and ages. Existing diagnostic techniques for heart failure have various limitations in the clinical setting and there is a need to develop a new diagnostic model to complement the existing diagnostic methods. In recent years, with the development and improvement of gene sequencing technology, more genes associated with heart failure have been identified. We screened for differentially expressed genes in h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 45 publications
0
0
0
Order By: Relevance
“…The DEGs associated with HF identified by Boyang et al through analysis of the Omnibus database included GLUL . 23 Huang et al reported that SRGN may be a new HF target in iDCM patients, 24 and our screening results were consistent with theirs, finding that GLUL and SRGN were differentially expressed in HF, while the gene was also differentially expressed in AF. Currently, no previous studies have identified the expression and function of GLUL and SRGN in AF, which is also an innovative aspect of this study, as it reveals the relationship between GLUL , SRGN , and AF for the first time.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…The DEGs associated with HF identified by Boyang et al through analysis of the Omnibus database included GLUL . 23 Huang et al reported that SRGN may be a new HF target in iDCM patients, 24 and our screening results were consistent with theirs, finding that GLUL and SRGN were differentially expressed in HF, while the gene was also differentially expressed in AF. Currently, no previous studies have identified the expression and function of GLUL and SRGN in AF, which is also an innovative aspect of this study, as it reveals the relationship between GLUL , SRGN , and AF for the first time.…”
Section: Discussionsupporting
confidence: 89%
“…In this study, we found four new biomarkers highly correlated with AF and HF, namely, GLUL , NCF2 , S100A12 , and SRGN , which is different from the results of Zhuang et al Proteins encoded by GLUL belong to the glutamine synthase family and play a role in acid–base homeostasis, cell signalling, and cell proliferation. The DEGs associated with HF identified by Boyang et al through analysis of the Omnibus database included GLUL 23 . Huang et al reported that SRGN may be a new HF target in iDCM patients, 24 and our screening results were consistent with theirs, finding that GLUL and SRGN were differentially expressed in HF, while the gene was also differentially expressed in AF.…”
Section: Discussionsupporting
confidence: 84%
“…SERPINA3 is a circulating acute-phase protein and endogenous inhibitor of serine proteases [57]. There is growing evidence that it could be a prognostic marker in cardiovascular disease [58][59][60][61][62]. Yet, its (patho)physiological role is poorly understood, and literature is often contradictory, stressing the need for further research.…”
Section: Serpina3 An Enigmatic Protein With Association To Ctr-cvtmentioning
confidence: 99%